Correlates of children’s cognitive skills in an agrarian community with mixed crop-livestock production systems, Ginchi, Central Ethiopia - Ketema, L.; Abate, G.; Jabbar, M.A. (2003)
A cross-sectional survey was carried out in Ghinchi farming community, central Ethiopia during October and November 2001 to assess the level of association between children's nutritional status, families' socio-economic gradient, and degree of maternal attention and cognitive development. Ninety children were enrolled in the study, and assessment for cognitive performance was carried out using Bailey Infant Development Scale II. A pilot tested questionnaire was used to collect data on socio-economic status, mothers' care behavior, sanitary conditions of households and feeding pattern, and anthropometry of children. Chronic malnutrition expressed as height for age < -2Z-score of standard was prevalent beginning from the second birthday. Poor cognitive performance was comparatively common in the age group where chronic malnutrition is proportionately prevalent. Logistic regression analysis for variables that demonstrated significant association in correlation study revealed height for age, household possession of consumable durables, maternal care time, type and frequency of feeding and birth order of the child to be significant determinants for cognitive performance of children. Findings implicate a need for comprehensive approach, which incorporates, programs in nutrition, environmental sanitation, family planning, and strategies to reduce maternal workload, to ensure adequate physical and mental development of children.